Evaluation of the biodiversity of arbuscular mycorrhizal fungi during regenerative succession in quarries - A. A. Kryukov; A. P. Yurkov; A. O. Gorbunova; T. R. Kudriashova; A. I. Gorenkova; Y. V. Kosulnikov; Y. V. Laktionov (Вавиловский журнал генетики и селекции, 2025)
Arbuscular mycorrhizal fungi (AMF) play a key role in the regenerative successions of plant communities after anthropogenic disturbances, particularly in quarries. AMF help plants with water and mineral nutrition, contributing to the restoration rate of vegetation cover.   The research is aimed to study the biodiversity of AMF using molecular genetic methods at different stages of overgrowth of two quarries in the Leningrad region.   Molecular genetic identification of fungi was carried out using Illumina MiSeq analysis of the ITS1 and ITS2 regions as barcodes for the identification of operational taxonomic units (OTUs) with species-level identification. An adapted and error-checked AMF genetic sequence database from NCBI was used as a reference. The study applied an optimized nucleic acid isolation technique for sandy soils. The results showed maximum AMF biodiversity at the initial stages of overgrowth – pioneer and grass stages – with minimum diversity observed at the shrub stage, where it decreased by five times. At the forest stage, the biodiversity of AMF was almost restored to the level seen at the grass stage. It has been shown that the biodiversity and species composition of AMF can vary greatly between the stages of regenerative succession and probably depends primarily on the biodiversity of grasses, with which AMF most effectively enter into symbiotic relationships. The analysis showed a reliable negative correlation between the number of AMF species and the number of woody plant species. Such studies can aid in understanding how plant-fungal symbiosis develops in regenerative successions and which AMF most effectively contribute to vegetation cover restoration.